Catalytic degradation of methylene blue using a newly engineered composite and its electrochemical performance - Ayesha Kiran; Muhammad Ramzan; Muhammad Faheem; Shabbir Hussain; Muhammad Imran (Case Studies in Chemical and Environmental Engineering, 2020)
Herein, we reported the development of tetramethoxyphenylporphyrin (CoTPP)/reduced graphene (rGO)/multiwalled carbon nanotubes (MWCNTs) composite via an ultrasonic treatment. The engineered composite was characterized by different analytical techniques like scanning electron microscopy (SEM), energy dispersive X-ray (EDX), ultraviolet–visible spectroscopy (UV–Vis) and Fourier transform infrared spectroscopy (FT-IR). The synthesized composite was tested for the catalytic degradation of methylene blue (MB) under solar irradiation and the electrochemical performance of the CoTPP/rGO/MWCNTs was also investigated in alkaline media by using cyclic voltammetry (CV). The photodegradation efficiency of prepared CoTPP/rGO/MWCNTs composite is 92% degradation of MB in water within 60 ​min irradiation. The results of the cyclic voltammogram showed that the onset potential value was -0.4 ​V while peak potential value of CoTPP-rGO/CNTs was -0.59 ​V. The high onset peak potential values and the current values of the CoTPP/rGO/MWCNTs make it a promising candidate as a catalyst for ORR.